Effect of dopamine agonists on fatigue and somnolence in Parkinson's disease - Oved, Daniel; Ziv, Ilan; Treves, Therese A; Paleacu, Diana; Melamed, Eldad; Djaldetti, Ruth (Movement disorders, 2006)
Dopamine agonists are becoming increasingly important in the treatment of early and advanced symptoms of Parkinson disease (PD). Although dopamine agonists are known to increase somnolence, their effect on fatigue and the relationship between fatigue and somnolence have not been investigated thoroughly. The objective of this study is to quantitatively measure fatigue in patients with PD treated with dopamine agonists and to correlate fatigue with somnolence. Fifteen patients with PD (mean age, 60.6 ± 9.7 years; mean disease duration, 4.1 ± 1.9 years) underwent a continuous (30‐second) motor task using four muscle groups before and after 3 months of treatment with dopamine agonists. A fatigue index, defined as the decay of maximal force during continuous exercise, was calculated. Findings were compared with 15 healthy, age‐matched control subjects. Patients also completed the Multidimensional Fatigue Inventory (MFI), the Epworth Sleepiness Scale (ESS), and the Hamilton Depression Scale at the same time points. Mean fatigue index (FI) before treatment was significantly higher in PD patients than controls (31.37% ± 3.81% vs. 23.39% ± 3.03%, P < 0.001). There was no significant between‐group difference after 3 months of treatment. There was no difference in FI of the more affected side before and after treatment (33.33% ± 6.18% vs. 34.08% ± 5.43%, P > 0.1). No significant change in MFI scores were noted after treatment, although scores on the ESS increased significantly (6.6 ± 2.63 vs. 11.7 ± 5.16; P < 0.05). Fatigue is prevalent in patients with PD but is not influenced by dopamine agonists. Somnolence cannot be attributed to the increase in fatigability and apparently involves a different mechanism. © 2006 Movement Disorder Society